Impactos da terceirizaç\~ao sobre a remuneraç\~ao do trabalho no Brasil: Novas evidências para o debate - André Gambier Campos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– This article brings new inputs to debate outsourcing in Brazil, using a new methodology based on administrative records. With this methodology, it is possible to identify 4.02 million outsourced workers, corresponding to 11.7% of total employees in the urban private sector. Moreover, with this methodology, it is possible to compare wages of direct and outsourced employees, noticing a negative dynamic in detriment of the latter. Other attributes also affect wages of outsourced employees, but outsourcing itself is an important factor that can "explain" variation in wages. Anyway, further studies are needed, focusing on the impact of outsourcing, before any decision about the subject. In particular, before any decision of the parliament, which is about to vote a new regulation on outsourcing in Brazil.
Keywords: J31; J38; J80; 330; outsourcing; employment; wage; regulation; State